Factors Affecting Eating Out in Restaurants: A Study on Customers of Dhaka City (Global Journal of Management and Business Research, 2020)
Eating out in restaurants is becoming a part of lifestyle among Bangladeshi citizens. While the popularity of eating out is increasing, parallelly, the number of restaurants has been rising at an astounding speed. Given the potential of the restaurant business in the country, this study investigates the reasons for which customers choose a particular restaurant to eat out and whether those reasons vary across demographic variables. Our study shows ambiance and quality of food are the top two factors that customers consider to choose a restaurant for eating out. It also shows that customers do not usually care much about menu variety, food presentation, and value-added deals. We found differences in preference exist among these factors across gender and age and showed the influence of gender and age on the frequency of visit and purpose of the visit. The findings of this study provide major implications for the marketers and entrepreneurs which we articulate at the end.
Keywords: Eating out; restaurant; factors; the influence of demographics; Bangladesh